Pengaruh Motivasi, Lingkungan Kerja dan Kompensasi Terhadap Kepuasan Kerja Guru di MAN 2 Rembang - Rahma Fitriyana; Syaiko Rosyidi (Economic Reviews Journal, 2026)
This study aims to analyze the effect of motivation, work environment, and compensation on teacher job satisfaction at MAN 2 Rembang. The population of this study consisted of all teachers with Civil Servant (PNS) and Government Employee with Work Agreement (PPPK) status, totaling 68 respondents, who were simultaneously used as the research sample through purposive sampling technique. Data were collected using a likert scale questionnaire that had been tested for validity and reliability. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results indicate that motivation, work environment, and compensation simultaneously have a significant effect on teacher job satisfaction. Partially, the work environment has a positive and significant effect on teacher job satisfaction, while motivation and compensation show a positive but not significant effect. The Adjusted R² value of 0.838 indicates that 83.8% of the variation in teacher job satisfaction is explained by motivation, work environment, and compensation, while the remaining 16.2% is influenced by other factors outside this study. These findings are expected to provide useful insights for school management in improving teacher job satisfaction.